(untitled) (Research, Society and Development, 2023)
SARS-CoV-2 consists of a virus that is part of the betacoronavirus family that causes the disease COVID-19, observed in patients with atypical pneumonia characterized by fever, dry cough and progressive dyspnea. In this bias, the virus carries single-stranded RNA with typical structural proteins, involving the envelope proteins (E protein), membrane (M), nucleocapsid (N) and spike (S), which cause viral infection. Regarding the complications of COVID-19, the impairment of the respiratory system is the main one, however, studies show the presence of coagulation disorders associated with the elevation of several biomarkers. Even though this pathological effect on the coagulation system is still not well evidenced, it is well known that the release of several pro-inflammatory cytokines, cell lesions in the vascular endothelium and platelet activation tend to play a crucial role in the process. In addition, one of the risk groups, obstetric patients, requires greater attention, due to the coagulation and hemostatic changes already expected in these patients. The research was carried out in Google Scholar, Virtual Health Library (VHL), Scientific Electronic Library Online (Scielo) and PubMed databases. In the current work, it will be approached through a bibliographic review, regarding the incidence of venous thromboembolism in pregnant patients infected with COVID-19. The aim of this study was to analyze the incidence of venous thromboembolism in pregnant patients infected with COVID-19. It was evident that pregnant women are a group more prone to complications, due to the hypercoagulability process. Furthermore, there is a need for further studies to address this association.